Performance and livestock producers’ integration into cattle and pig farmer groups in NWH Vietnam - Bravo, Aura; Thinh Nguyen; Phuong Nguyen; Triana Ángel, Natalia; Tran The Cuong; Pham-Van Hung; Nga Nguyen; Huyen Nguyen; Marshall, Karen; Burkart, Stefan (International Center for Tropical Agriculture, 2023)
Farmer groups in Vietnam have undergone considerable transformations following the enforcement of the 2012 Law on Cooperatives. Under the new regulations, the old cooperative model became obsolete, which led to the disintegration or stop operation of numerous organisations. This gave way to a developing process of new forms of association in agricultural production, a field open to exploration. Within an evolving economy with greater exposure to international markets, adopting a scheme based on collective voluntariness reveals a challenging path for agricultural production’s social organisation, even more so if the individual perspectives of stakeholders on the performance and convenience of these groups are considered. Previous interventions have promoted the creation of farmer groups in Vietnam’s Northwest Highlands (NWH) to foster associativity, facilitating connection to markets and economies of scale for services, technologies, and knowledge transfer to livestock farmers. This research thus provides an assessment of the functioning and capacities of farmer groups engaged in cattle and pig production. To this end, five components were defined based on tools commonly used for strengthening farmer groups: 1) democratic, inclusive, and participatory management, 2) service offer and capacity building, 3) economic and financial sustainability, 4) managerial and administrative capacity, and 4) market connections and trading capacity. This approach integrates the analysis of behavioural elements from members, non-members, men, women, and local authorities on the perceived trust and commitment to participate in existing forms of cooperation. Information was collected through focus groups discussion and key informant interviews. The findings are currently being analysed and will allow researchers to design interventions aimed at strengthening farmer groups. They will too serve as input for current efforts to develop innovative models to deliver and scale innovations towards sustainable livestock production, replicable in other regions.